Cr2O3:TiO2 Nanostructure Thin Film Prepared by Pulsed Laser Deposition Technique as NO2 Gas Sensor - Saadoon M. Kareem et al. (مجلة بغداد للعلوم, 2020)
Pulsed laser deposition (PLD) technique was applied to prepared Chromium oxide (Cr2O3) nanostructure doped with Titanium oxide (TiO2) thin films at different concentration ratios 3,5,7 and 9 wt % of TiO2. The effect of TiO2 dopant on the average size of crystallite of the synthesized nanostructures was examined by X-ray diffraction. The morphological properties were discussed using atomic force microscopy(AFM). Observed optical band gap value ranged from 2.68 eV to 2.55 eV by ultraviolet visible(UV-Vis.) absorption spectroscopy with longer wave length shifted  in comparison with that of the bulk Cr2O3 ~3eV. This indicated that the synthesized samples are attributed to the enhancement of the quantum conﬁnement effect. Gas response sensitivity, and recovery times of the sensor in the presence of NO2 gas were studied and discussed. In this work it is found that, the sensitivity increases when doping ratio increases from 3wt% to 5wt% of TiO2  and return to decrease over that. The optimum concentrations ratio for NO2 gas sensitivity is 5wt% of TiO2  and sensitivity is 168.75% at 200oC.